Pemberdayaan Ekonomi Pesantren melalui One Pesantren One Product (OPOP) di Ponpes Kawasan Pantura Lamongan - Amalia, Dini; -, Shofiyah; Rif'ah, Sifwatir; Sa'idaturrohmah, Nur (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
The Covid pandemic has had a huge impact on Indonesia's Economy. UMKM boarding school was adversely affected. OPOP becomes one of the beneficial ways to revive this situation. Unfortunately, many boarding schools in East Java still have no experience joining OPOP. Hence, this Madrasah and Pesantren-based program urgently needs to be conducted. The accompaniment aims to optimize three boarding schools' products and economic potential on the North Coast of Lamongan. They are Maslakul Huda, Mazraatul Ulum, and Raudlatut Thullab boarding schools. This program applies the ABCD method and appreciative inquiry approach. The result signifies that all students, alums, and the boarding school can synergize more optimally to establish better financial management, marketing, and packaging products and enhance the understanding of benefits, strategy, and OPOP membership. In short, they perceive the accurate way to thoroughly improve their economic potential to realize a more empowered boarding school and prosperous society.